2014
DOI: 10.1016/j.rvsc.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation and analysis of the immune response in calves from vaccinated pregnant cows

Abstract: The effect of vaccinating pregnant cows with an inactivated vaccine against Mannheimia haemolytica, BRSV and PI3V infections on selected immune responses in their offspring was examined. Blood samples were collected weekly for 12 weeks from six newborn calves from each of vaccinated (experimental) and unvaccinated (control) dams. Specific antibodies to M. haemolytica, BRSV and PI3V and mean values of IgA, IgG concentrations were significantly higher in the experimental calves compared with the controls. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…Significantly (P = 0.0021; P = 0.0013) elevated titres were also observed at PVD120. These findings are in agreement with those of other studies in which an increased colostral antibody production against BoHV-1 and various pathogens were detected after the vaccination of pregnant cattle during the pre-partum period [13,21,22,27]. In contrast, in a study conducted by Lemaire et al, a low level of antibodies against BoHV-1 was observed in two cows after two vaccinations with inactivated gE-deleted marker vaccines [28].…”
Section: Discussionsupporting
confidence: 92%
“…Significantly (P = 0.0021; P = 0.0013) elevated titres were also observed at PVD120. These findings are in agreement with those of other studies in which an increased colostral antibody production against BoHV-1 and various pathogens were detected after the vaccination of pregnant cattle during the pre-partum period [13,21,22,27]. In contrast, in a study conducted by Lemaire et al, a low level of antibodies against BoHV-1 was observed in two cows after two vaccinations with inactivated gE-deleted marker vaccines [28].…”
Section: Discussionsupporting
confidence: 92%
“…O bezerro VAC 10 manifestou infecção natural ao BPI3-V entre o D10 e o D15 (Martin e Bohac, 1986). Dudek et al (2014) encontraram maiores concentrações de ACs séricos contra o BRSV e o BPI3-V em filhos de vacas vacinadas no período pré-parto, porém estes autores detectaram os ACs séricos pelo teste imunoenzimático indireto, que geralmente é mais sensível que a VN (Brodersen, 2010;Ellis, 2010). Em geral, os bezerros apresentaram perfil sorológico semelhante às suas mães.…”
Section: Resultsunclassified
“…BoHV-1 virus causes respiratory infections and abortions in cattle, and is an important component of the bovine respiratory disease complex, which causes a considerable economic loss worldwide (Chowdhury, Wei, Weiss, Pannhorst, and Paulsen, 2016). Pre-partum vaccination programs have been reported to increase colostral antibodies and protect newborn calves from viruses associated with calf pneumonia, for example, Mannheimia haemolytica, BRSV, and PI3V (Makoschey, Ramage, Reddick, Fraser, and Donachie, 2012;Dudek, Bednarek, Ayling, and Szacawa, 2014). M. haemolytica is a primary bacterial pathogen associated with BRD (Reddy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%